2021
DOI: 10.2174/0929867328666210211164314
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Anticancer Activity of Hybrid Molecules and Derivatives based on 5-Fluorouracil

Abstract: : Cancer still continues as an important cause of death worldwide. Thus, several conventional anticancer treatments are widely used, however, most of them display low selectivity against malignant cells and induce many adverse side effects. Among these, the use of therapies based on 5-Fluorouracil (5-FU) has been one of the most efficient, with a broad-spectrum. Due to these circumstances, various modifications of 5-FU have been developed to improve drug delivery and reduce side effects. Among the optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…However, this compound not only exhibits a short half-life and low selectivity but also different grades of toxicity including neurological, gastrointestinal disorders and myelosuppression, among others, which leads to dose limitation and treatment discontinuation [ 2 ]. For these reasons, this molecule has been extensively modified to obtain conjugates and hybrid molecules, which may improve its therapeutic potential and selectivity, leading to a decrease in side effects [ 3 ]. In addition, several natural products have been evaluated since they exhibit a plethora of biological activities in different in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this compound not only exhibits a short half-life and low selectivity but also different grades of toxicity including neurological, gastrointestinal disorders and myelosuppression, among others, which leads to dose limitation and treatment discontinuation [ 2 ]. For these reasons, this molecule has been extensively modified to obtain conjugates and hybrid molecules, which may improve its therapeutic potential and selectivity, leading to a decrease in side effects [ 3 ]. In addition, several natural products have been evaluated since they exhibit a plethora of biological activities in different in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, hybrid F was evaluated on SW480 cells, and the results showed that 48 h post-treatment with 300 µM it displayed significant activity over SW480 cells, causing a significant reduction in cell viability (40.49%), in a time- and concentration-dependent manner [ 18 ]. Many other examples of hybrid molecules based on 5-FU conjugated with both natural and synthetic compounds, together with their biological activities on different models of cancer, were summarized by Cardona et al, 2021 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of hybrid compounds has emerged as a promising strategy in medicinal chemistry and drug discovery research. This design is based on the covalent linking of two molecules with individual intrinsic pharmacological activity [ 21 , 22 ]. The combination of two pharmacophores with different biological activities, probably acting on different targets, could confer a dual activity to the molecule [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of hybrid compounds has emerged as promising strategy in medicinal chemistry and drug discovery research, since these compounds combine two distinct biologically active molecules into one entity that can act on different targets, displaying a dual effect [24][25][26][27][28]. We have previously reported on the biological activity of different hybrids based on S-allyl cysteine ester-caffeic acid amides, using a colon cancer cell line.…”
Section: Introductionmentioning
confidence: 99%